Effects of various work-to-rest ratios during high-intensity interval training on athletic performance in adolescents - Seo, M.-W.; Lee, J.-M.; Jung, H. C.; Jung, S. W.; Song, J. K. (International Journal of Sports Medicine, 2019)
To examine the effect of high-intensity interval training (HIIT) with different work-to-rest ratios on athletic performance in athletes. Forty-seven male Taekwondo athletes (aged 15-18?yrs) were randomly assigned into 3 HIIT groups and a control group. Each group performed 6 and 8 bouts of HIIT: 1) 1:2 (30:60 s), 2) 1:4 (30:120 s), and 3) 1:8 (30:240 s) groups while the control group performed only Taekwondo training program. All HIIT groups completed 10 sessions over 4 weeks. Athletic performance tests including VO2max test, Wingate anaerobic test, vertical jump, and agility T-test were measured at both pre- and post-tests. Two-way repeated measures ANOVA were applied to examine the performance changes between protocols. VO2max improved significantly in all HIIT groups (p<0.01), and the post-hoc test indicated that the only 1:4 group showed significant improvement compared to the control group. The HIIT with 1:4 ratio showed the effective protocol for enhancing anaerobic capacity including relative peak and mean power compared to control (p<0.01). Ten sessions of HIIT involving the 1:4 group, lasting over a brief 4-week period revealed the effective protocol for enhancing both aerobic and anaerobic capacity. Our findings provide practical implications to develop a performance-enhancing program specialized for adolescent Taekwondo athletes.